Patent vitelline duct as a cause of acute abdomen: Case report of an adult patient - Arsenal SEZGİN,; Bahri CAKABAY,; Yasemin DOLEK,; Sami AKBULUT,; Feride ALEVLİ, (Turkish Journal of Gastroenterology, 2019)
-